The existence of grebeg makukuhan on socio-cultural values of generation-Z in Kedu Village, Temanggung Regency - Putri, Sella Ewinda; Utomo, Cahyo Budi; Husain, Fadly (Universitas Negeri Semarang, 2022)
The development of information technology has caused the disappearance of the noble values of local culture. Grebeg Makukuhan is a local culture of Kedu Village that has socio-cultural values and various meanings from the symbols used by the community to instill noble and moral values in generation z. This study aimed to analyze the symbolic meaning in the implementation of Grebeg Makukuhan, how the Z-generation interprets the symbolic elements, and the role of parents in the inheritance of socio-cultural values. This research used qualitative research with an ethnographic approach. The results showed that the z-generation was able to maintain the existence of Grebeg Makukuhan with evidence that the z-generation children could explain the meaning of the symbol elements used in Grebeg Makukuhan activities. The findings that researchers can find in the form of success in maintaining cultural values can not be separated from the role of parents, thus positively impacting the development of Generation Z as the next generation and becoming good citizens who care about the environment. The general public can use the benefits of this research to study the methods used by Kedu Village people to maintain a local culture in the younger generation.